Sociological Research of a New Model of Professional Development of Library and Information Specialists in the Samara Region - I. N. Klyuyashkina; I. A. Bogdanova (Библиосфера, 2022)
The article is devoted to the results of a sociological study conducted within the framework of the innovative educational project “Federal Innovation Platform “Academy of Library and Information Skills” of the Samara State Institute of Culture. This innovative educational project is aimed at creating a new model of the professional development system and developing the creative potential of library and information specialists in the Samara region.The article highlights the advantages and disadvantages of the organization of professional development of library and information specialists in the region, outlines the prospects for the development of this activity, allowing the design of a new additional educational program “Modern library in the digital space”.The problem of improving the system of advanced training of library and information specialists of municipal libraries in the context of the formation of new professional competencies in the digital environment and the influx of specialists with non-core education to library institutions needs to be solved.